Names of Martial Figures in the Kang-Ouw World (World of Martial Arts) in China (China) - Salim, Agus; Muallimah, Eka Nurul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research is entitled "Names of Martial Figures in the World of Kang-Ouw (World of Martial Arts) in China, China: An Anthropologist Research". This research focuses on searching for the names of these terms and explanations regarding these names. This research is qualitative descriptive research. The data collection method in this research uses the listening method. The technique used for data collection is note-taking technique. The research data obtained is in the form of words or phrases which have become nicknames or nicknames for figures in the world of martial arts in China. The data source in this research is the silat story by Kho Ping Hoo entitled Bu Kek Sian Su. The theory used in analyzing the data is anthropo linguistic theory. This research aims to find out and explain what customs, ethnic habits and cultural patterns are behind the use of these names. From the results of the research conducted, researchers found that there are many names used by one person to another. This nickname is given because there is a relationship with the person who says it or there is a quality or background in the person mentioned. The results of the research findings along with the language data are presented in table form, to further simplify the discussion considering the limited space available.